Editorial as a Discursive Genre - E. A. Nikonova (Научный диалог, 2023)
Editorial is considered as a discursive genre of the English-language press. The concept of the discursive genre was developed by M. Montgomery on the example of mass media texts and allows us to combine the approach to considering the genre, on the one hand, as a recurrent stable structure, and on the other hand, to emphasize its mobility and variability. It is argued that this approach is especially relevant for media texts due to the existing difficulties in developing their typology and determining their status. The genre-forming features of editorial are highlighted: the use of colloquial speech, argumentativeness, intertextuality, high emotionality of the language, the presence of individual author’s nominations, as well as the use of discursive practices of recommendation and forecasting. The structure of the genre is defined: it is a three-stage model, where the conclusion plays a special role, which, in turn, can take such forms as conclusion-recommendations, conclusion-forecast, conclusion-evaluation, as well as various combinations of all three types of conclusions. It has been established that, from the point of view of content, the editorial covers the most pressing issues that are at the center of socio-political debates. The definition of editorial is given as a genre of high-quality English-language press, which acts as a tool for promoting the political interests of the newspaper and influencing public values and attitudes.